1987
DOI: 10.1152/ajpendo.1987.253.2.e202
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal Ca2+ transport in streptozotocin-induced diabetic cardiomyopathy in rats

Abstract: Heart sarcolemmal membranes were isolated by the sucrose density gradient method from rats with chronic diabetes induced by a streptozotocin (65 mg/kg iv) injection. Na+-dependent Ca2+-uptake activities were significantly depressed in diabetic sarcolemmal membranes; such alterations were evident at different incubation times and at different concentrations of Ca2+. Administration of insulin to diabetic rats normalized the Na+-dependent Ca2+-uptake activities. ATP-dependent Ca2+ accumulation and Ca2+-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
0
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 22 publications
6
69
0
1
Order By: Relevance
“…These findings are in agreement with the results reported by DeBlieux et al (13) showing a slight reduction in cardiac output and no changes in other indices of cardiac work in diabetic rats. However, reduction in myocardial performance has been previously reported (12) and several authors (24,25) have demonstrated that these changes may be related not only to depressed myosin ATPase but also to decreased calcium uptake by the sarcoplasmic reticulum (13). However, the most impressive finding in the present study is that exercise training reverses the changes in contractile properties of the heart induced by STZdiabetes in rats.…”
Section: Discussionsupporting
confidence: 51%
“…These findings are in agreement with the results reported by DeBlieux et al (13) showing a slight reduction in cardiac output and no changes in other indices of cardiac work in diabetic rats. However, reduction in myocardial performance has been previously reported (12) and several authors (24,25) have demonstrated that these changes may be related not only to depressed myosin ATPase but also to decreased calcium uptake by the sarcoplasmic reticulum (13). However, the most impressive finding in the present study is that exercise training reverses the changes in contractile properties of the heart induced by STZdiabetes in rats.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, hyperglycaemia promotes the cascade of further signalling and metabolic abnormalities e.g. increased pro- duction of oxygen free radicals and reduced antioxidative defence [31,32], defects in intracellular Ca handling [33] which may have additional destructive effects on the function of capillary endothelium. NO-deficient hypertension is also accompanied by various metabolic disturbances, including enhanced production of oxygen free radicals [34], reduced activity of Na, K-ATPase [35], and increased lactate dehydrogenase activity [9] which may contribute to endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in view of the role of SR in cardiac contraction and relaxation processes, the observed reduction in SR function may explain the depressed cardiac performance in diabetic animals. Such a view does not exclude other mechanisms, such as depressed myofibrillar ATPase (18) -pump and Na ϩ -Ca 2ϩ exhange activities (20), which have been shown to contribute to cardiac dysfunction in the diabetic heart. Current evidence favors enhanced SR Ca 2ϩ -uptake under physiological conditions as a consequence of phosphorylation of the SERCA2a by CaMK (14) and phosphorylation of PLB by both CaMK and PKA (21)(22)(23).…”
Section: Diabetes Vol 50 September 2001mentioning
confidence: 99%
“…Because the treatment of STZ-induced diabetic rats with insulin has been reported to prevent diabetes-induced changes in the heart (3)(4)(5)(6)(17)(18)(19)(20), it is likely that insulin deficiency may play a role in regulating cardiac protein content. Increased proteolysis shown to occur in the diabetic heart (34) is reduced by insulin (35).…”
Section: Diabetes Vol 50 September 2001mentioning
confidence: 99%